The impact of vitamin K standardization in hospital diets: DOI: 10.15343/0104-7809.20174103333342 - Guedes Miranda, Bárbara Cristina (2017)
A prospective controlled study evaluating the impact of standardized dietary modifications on vitamin K levels in hospital diets of chronic oral, anticoagulated patients, using warfarin. The intervention group received a diet with a standardized content of vitamin K and the control group received a diet without this standardization. In both, the International Normalized Ratio (INR) was performed according to the medical staff’s protocol, without interference from the research group members. Data on dietary intake of vitamin K, INR, warfarin dosage, and the time taken for normalization of INR were collected. Food intake was evaluated by a 24-hour food recall, starting from the beginning of warfarin use until the normalization of INR. The sample consisted of 55 patients, 29 patients in the control group and 26 patients in the intervention group. The average age was 55.47 ± 17.52 years old, 56.3% were female, and 49.1% were elderly. The coefficient of variation in the consumption of vitamin K was significantly higher in the control group (0.45 ± 0.22) compared to the intervention group (0.31 ± 0.19); p = 0.018. The average dosage of warfarin use was significantly lower in the intervention group (5.30 ± 1.42 mg / day) compared to the control group (6.21 ± 1,84mg / day); p = 0.044. The data showed that a hospital diet with standard amounts of vitamin K reduces the warfarin dosage to normalization of INR in oral anticoagulated patients. This result can reduce the risk of bleeding events, especially in the elderly.